Residual Periodontal Ligament Levels in Extracted Teeth of Chronic Periodontitis Patients with Type 2 Diabetes Mellitus - Kaushik Vishnu Rajkumar; Dr. Dinesh Kumar (Revista Electronica de Veterinaria, 2023)
This in vitro study investigates the impact of type 2 diabetes mellitus (T2DM) on residual periodontal ligament (RPL) levels in extracted teeth of chronic periodontitis patients aged 50–60 years. Fifty teeth (25 from diabetic patients with HbA1c ≥6.5% and 25 from non-diabetic controls with HbA1c <5.7%) were analysed. RPL levels were measured using haematoxylin staining and digital callipers, with comparisons between groups assessed via Mann-Whitney U tests. Diabetic patients exhibited significantly lower overall RPL levels (0.69 ± 0.25 mm vs. 0.94 ± 0.32 mm, *p=0.012*), with pronounced reductions in incisors (−48%) *p=0.018*) and premolars (−32%). *p=0.006*). Stratification by HbA1c revealed a non-significant trend of declining RPL with worsening glycemic control (*p=0.542*). These findings underscore the systemic impact of T2DM on periodontal integrity, likely mediated by hyperglycemia-induced oxidative stress and impaired collagen remodelling. Despite limitations in sample size and cross-sectional design, the study highlights the need for integrated diabetes-periodontal care to mitigate tooth loss. Further research with longitudinal designs and inflammatory biomarkers is warranted to elucidate causal mechanisms.